Pengaruh Kualitas Pelayanan dan Harga Terhadap Kepuasan Konsumen pada Layanan Go-Food Di Kota Pekanbaru - Komalasari, Eka; Sintari, Riska (Jurnal Sekretaris dan Administrasi Bisnis, 2024)
This study aims to determine the effect of service quality and price on the satisfaction of Pekanbaru consumers who use Go-Food services. This type of research is associative with a quantitative method approach. The population in this study were all people of Pekanbaru City who had ordered and used Go-Food services. The sample in this study amounted to 100 respondents who were taken using a purposive sampling technique. Data was collected by distributing online questionnaires through Google Forms. The data analysis technique used in this research is validity test, reliability test, normality test, multicollinearity test, multiple linear regression analysis, t test and f test. The results showed that service quality has a positive and significant effect on consumer satisfaction, price has a positive and significant effect on consumer satisfaction. The results of the f test indicate that service quality and price have a simultaneous effect on customer satisfaction. The results of the coefficient of determination show that the value of r square is 0.678, which means that the service quality and price variables can affect customer satisfaction by 67.8% while the remaining 32.2% is influenced by other variables not examined in this study (such as: product quality, emotional and cost).